HOXA13 promotes immune evasion in bladder cancer by suppressing antigen processing and presentation, and phagosome pathways - Chin, Fee Wai; Chan, Soon Choy; Chau, De Ming; Ong, Teng Aik; Abdul Razack, Azad Hassan; Yusoff, Khatijah; Veerakumarasivam, Abhi (Springer Nature, 2025)
Homebox A13 (HOXA13) and homeobox B13 (HOXB13) expression dysregulation have been previously reported in bladder cancer. However, their roles in bladder carcinogenesis remain unclear. This study characterizes the distinct transcriptomic profile and pathway enrichment of HOXA13 and HOXB13 knockdown in bladder cancer cells. Separate in vitro knockdown models for HOXA13 and HOXB13 were established using small interfering RNAs (siRNAs), and knockdown efficiency was validated through reverse transcription-quantitative polymerase chain reaction (RT-qPCR). Transcriptomic profiling was conducted using RNA sequencing, followed by differential gene expression analysis, and Kyoto Encyclopedia of Genes and Genome (KEGG) pathway enrichment analysis. HOXA13 knockdown significantly enriched pathways that are associated with immune evasion (i.e. antigen processing and presentation pathway, and phagosome pathway) through the upregulation of major histocompatibility complex (MHC) class I and II genes. These findings highlight the pivotal role of HOXA13 in promoting immune evasion in bladder cancer. Meanwhile, HOXB13 knockdown significantly enriched estrogen signaling pathway and PI3K-Akt signaling pathway, which are critical for cell proliferation and survival. While the role of HOXB13 in bladder cancer progression requires further delineation, the primary focus of this study is on HOXA13 due to its involvement in immune evasion mechanisms. This study provides novel insights into the potential therapeutic strategies for targeting HOXA13 in bladder cancer, and highlights the distinct roles of HOXA13 and HOXB13 in bladder carcinogenesis.